Clinical course and long-term outcome following venoarterial extracorporeal life support-facilitated interhospital transfer of patients with circulatory failure. (August 2015) - Schopka, Simon; Philipp, Alois; Hilker, Michael; Müller, Thomas; Zimmermann, Markus; Arlt, Matthias; Rupprecht, Leopold; Schmid, Christof; Lunz, Dirk
Abstract: Background: Interhospital transfer of patients experiencing circulatory failure and shock has a significant risk of cardiovascular deterioration and death. Extracorporeal life support (ECLS) is a rescue tool for hemodynamic stabilization that makes patient transportation much safer. Methods: Demographic data, clinical course, and outcome data were reviewed for patients who underwent placement of a venoarterial ECLS in a remote hospital and were transported to our tertiary care facility. Results: 68 patients were transported to our center with ECLS. The majority of these patients (79%) underwent cardiopulmonary resuscitation during or immediately prior to ECLS initiation. The mean patient age was 52 years, and 53 patients were male. The most common underlying diagnosis was acute coronary syndrome (60%). Overall, 23 patients underwent consecutive cardiosurgical procedures, including coronary artery bypass grafting in 12, and left ventricular assist device and biventricular assist device implantation in 11. The median duration of ECLS was 5 days. None of the patients died during transportation. Twelve of the surgically treated patients survived, as well as 21 patients with non-surgical treatment, which resulted in an overall survival of 33 patients (48.5%). Conclusion: ECLS-facilitated patient transfer enables safe interhospital transfer of critically ill patients. In this study, a relevant percentage of patients were in need of a cardiosurgical intervention. The long-term survival rate of these patients supports the further use of this time-, cost- and personnel-demanding strategy.